Relationship between dynamic electrocardiogram and CRP, IL-6, ET-1 expression in myocardial ischemia patients with coronary heart disease: DCG and CRP, IL-6, ET-1 expression in PWMI with CHD - You, Lin (Cellular and Molecular Biology, 2023)
This study aimed to observe the relationship between dynamic electrocardiogram and CRP, IL-6, and ET-1 expression in individuals with myocardial ischemia and Coronary Heart Disease (CHD). For this purpose, from January 2021 to December 2022, 80 patients with CHD were admitted to the hospital to determine the presence of myocardial ischemia according to coronary angiography. The individuals were separated into a myocardial ischemia group and a no myocardial ischemia group. Dynamic electrocardiogram (DCG), serum CRP, IL-6, and ET-1 were used in the two groups, respectively. The association between dynamic electrocardiogram indexes and serum CRP, IL-6, and ET-1 levels was discovered using a Pearson correlation analysis. Results showed that the SDNN, SDANNI, rMSSD and PNN50 of Patients with Myocardial Ischemia (PWMI) were lower than individuals with CHD without myocardial ischemia (P<0.05). CRP and IL-6 were negatively correlated with SDNN, SDANNI, rMSSD and PNN50 (P<0.001). ET-1 had a bad relationship with rMSSD and PNN50 (P<0.001). Correlation heat map analysis showed that the color difference of IL-6 was the most obvious between PWMI and Patients Without Myocardial Ischemia (POMI), and IL-6 was more strongly correlated with dynamic electrocardiogram-related indexes of myocardial ischemia. In individuals with CHD myocardial ischemia, there is a negative connection between the DCG index and the production of the inflammatory cytokines CRP, IL-6, and ET-1. In conclusion, CRP, IL-6, and ET-1 levels should be monitored in patients with decreased heart rate variability, so as to further determine the level of micro-inflammation and endothelial function.